2018
DOI: 10.1515/hukin-2017-0175
|View full text |Cite
|
Sign up to set email alerts
|

How To Maintain Maximal Straight Path Running Speed on a Curved Path in Sprint Events

Abstract: This study aims to clarify the ideal technique for running on a curved path during sprinting events. Participants were twelve male track and field athletes including long jumpers and sprinters. The participants performed a 60-m sprint with maximal effort on straight and curved paths. Participants were divided into “good curve runners” and “poor curve runners” according to the curved path running speed relative to that of the straight path. Kinematic variables and ground reaction forces (GRFs) were registered a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Final times are: 20.43 for the straight track, 20.46 for lane 8, and 20.48 for lane 1. Let us point out that our simulations are consistent with the experiments in [3], where runners are asked to run 60m on a straight path and on a curved path. The authors observe the existence of two groups, one "good" group who manages to reach the same velocity in the curved path as in the straight path and the other "poor" group who is strongly affected by the curve.…”
Section: Single Runner On a Standard Curved Tracksupporting
confidence: 83%
See 1 more Smart Citation
“…Final times are: 20.43 for the straight track, 20.46 for lane 8, and 20.48 for lane 1. Let us point out that our simulations are consistent with the experiments in [3], where runners are asked to run 60m on a straight path and on a curved path. The authors observe the existence of two groups, one "good" group who manages to reach the same velocity in the curved path as in the straight path and the other "poor" group who is strongly affected by the curve.…”
Section: Single Runner On a Standard Curved Tracksupporting
confidence: 83%
“…To our knowledge, no optimal control problem including these effects has been studied. There is a huge literature on the way of running on a curved track, see for instance [1][2][3][4][5][6][7][8]. Nevertheless, it is never coupled with the psychological effect to have a neighbor on the next lane, which is mentioned as important.…”
Section: Introductionmentioning
confidence: 99%
“…ences between the linear and "weak" side curve sprint (1.2 % difference), as well as between the "good" vs. "weak" side curve (1.6 % difference) (▶ table 1). Previous research reported similar results between curve and linear performance with no differences between both actions [28]. Conversely, a study [17] reported superior performances in linear sprints (30 m) in comparison with curve sprints.…”
Section: Performance Analysismentioning
confidence: 71%
“…What about if the secret behind beating records was to build a new athletic track with a better geometry? Researchers have addressed theoretical issues on various aspects of sport records [1][2][3][4][5] or strategies [6][7][8][9][10], on the effect of running on a bend [11][12][13][14][15], however, little has been done on how to improve the records for running 200 m. Indeed, the more economical way to run is on a straight, but only the 100 m is run straight. Starting from 200 m, the track has curved parts so that the runner has to counter the centrifugal force and inner lanes are therefore disadvantaged.…”
Section: Introductionmentioning
confidence: 99%